Perceraian Berdasarkan Perspektif Teori Struktural Fungsional dan Teori Konflik Sosiologi Modern - Rr. Aisa Kartika Puspita Dewi; Nita Puspita Dewi; Dina Rizqayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In married life between husband and wife it is possible for problems or problems to be found and solutions that are difficult to find solutions to. As soon as a solution is not found and a settlement is also not available, a husband or a wife can think of taking the middle way, namely divorce. This writing uses normative qualitative research methods. Normative qualitative research is research carried out by means of research on library materials or library research approaches. The modern sociological approach, namely structural-functional theory and conflict theory, is part of family relations within the community environment, clearly explaining how social processes occur within a family relationship within the community environment itself. Separation, another form of divorce between husband and wife, can be interpreted properly and positively. When they are more willing to live a new life, they can also maintain integrity as parents of their children. Maturity is able to change from someone with a partner who experiences problems and problems, into a partner who is able to work together for the sake of the continuity of the family whole even without the status of a husband and a wife.